The Effect of Social Media Political Marketing on Trust, Knowledge and Voting Intention of Youth Voters: Study of Indonesia Presidential Election 2019 - Annisa, Luna B1024151004 (Jurnal Manajemen Update, 2019)
Abstract: This research devoted to analyze relationship between social media political marketing through trust, knowledge & voting intention of youth voters, regarding with Indonesia Presidential Election 2019. In total hundreds of respondents, with 51 women and 49 men, thus majority are Tanjungpura University students. With age 17-35 as young adults, actively on social media, indeed aware with presidential candidates 2019 of political marketing, for at least six months. By using online questionnaire and spread through social media, the data processed with SmartPLS 3.2.8. software. The methods is a causal research, based on Likert seven-point scale. Results, however revealed no significant relationship between social media political marketing with youth voting intention (H3). And four hypotheses is accepted and positively correlated, and trust consider as partially mediation of social media political marketing on youth voting intention.Keyword: social media, political marketing, voter trust, voter knowledge, voting intention, indonesia presidential electionReferencesAbdillah, L. A. (2014, September 22). Indonesian's Presidential Social Media Campaigns.Abdillah, W., & Hartono, J. (2015). Partial Least Square (PLS): Alternatif Structural Equation Modelling (SEM) dalam Penelitian Bisnis. Yogyakarta: Penerbit Andi.Ahmed, M. A. (2017). Political Marketing: Role of Socialization Process In The Evelopment Of Voting Intention. International Academic Conference. London: University of Gujarat.Al-Mohammad, S. M. (2017). The Impacts of Social Websites Over Jordanian Students' Intentions of Active Political Participation: An Application of Theory of Planned Behavior. International Review of Management and Marketing , 1-16.Alreck, P., & Settle, R. (2003). Survey Research Handbook (3rd ed). Newyork: Mcgraw-Hill Education.Andi Alimuddin, S. (2016, August). The Internet and Social Media in Political Participation in Indonesia. International Journal of Management and Applied Science .Aprianingsih, W. G. (2015). Factors Influencing Voting Intention For Indonesian People's Representative Council Election 2019: The Case of First Voter In. Journal of Business and Management, 4, 675-693.Baron, R. M., & Kenny, D. A. (1986). The Moderator-Mediator Variable Distinction in Social Psychological Research: Conceptual, Strategic, and Statistical Considerations. Journal of Personality nd Social Physchology , 51 (6), 1176.Bathelt, S. (2015). Political Knowledge - Mediator of Political Participation? Montreal, Canada: General Conference of the European Consortium for Political Research (ECPR).Bigi, A. (2017). Political Marketing: Understanding and Managing Stance and Brand Positioning. Doctoral Thesis, Industrial Marketing, Stockholm, Sweden.Biswas, A. I. (2014). Influence of Social Media on Voting Behaviour. 127-155: Journal of Power.Blais, C. H. (2010, September 1-5). Intention to vote, reported vote and validated vote.Boro, V. I. (n.d.). Pemasaran Politik Legislatif Petahana Dalam Memenangkan Pemilu Anggota DPRD Kota Kupang Provinsi Nusa Tenggara Timur Tahun 2009 (Kajian Strategi Politik dan Bauran Produk Politik).Boulianne, S. (2008). Does Internet Use Affect Engagement?Cangara, H. (2009). Komunikasi Politik: Konsep, Teori dan Strategi. Jakarta: Rajawali Press.Cooper, D. R., & Schindler, P. S. (2014). Business Research Methods. Newyork: McGraw-Hill/Irwin.Dabula, N. The Influence of Social Media Political Marketing on Trust, Loyalty and Voting Intention of Youth Voters in South Africa. South Africa.Dafler, F. (2013, April 23). Terindah. Retrieved from Memahami dan Mempelajari SmartPLS: http://feroniadafler.blogspot.co.id/2013/04/mempelajari-dan-memahami-smartpls.htmlDaniela Dimnitrova, A. S. (2014). The Effects of Digital Media on Political Knowledge and Participation in Election Campaigns: Evidence from Panel Data.Dimock, M. (2019, January 17). Defining generations: Where Millennials end and Generation Z begins. Retrieved December 22, 2018, from Pew Research Center: https://www.pewresearch.org/fact-tank/2019/01/17/where-millennials-end-and-generation-z-begins/Donner, M. W. (2009). Read-Write-Erase: Mobile-mediated publics in South Africa's 2009 Elections.Effing R., H. J. (2011). Social media and political participation: are Facebook, Twitter and YouTube democratizing our political systems? Electronic Participation Lecture Notes in Computer Science.Firmanzah. (2008). Marketing Politik: Antara Pemahaman dan Realitas. Jakarta: Yayasan Obor Indonesia.Firmanzah. (2008). Marketing Politik; Antara Pemahaman dan Realitas. Jakarta: Yayasan Obor Indonesia.Fung, H. P. (2017). How do you determine the validity and reliability of a new questionaire? Online. Available at: https://www.reserachgate.net/post/How_do_you_determine_the_validity_of_a_questioanire , Accessed on 21 January 2019.Garnesia, I. (2018, September 12). Sana Sini Ngaku Milenial Bagaimana Peta Milenial Indonesia. Retrieved January 01, 2019, from Tirto: https://tirto.id/sana-sini-ngaku-milenial-bagaimana-peta-milenial-indonesia-cX5WHair, J., & Celsi, M. (2011). Essentials of Business Reseach Methods. Newyork: M.E Sharpe.Hanlong Fu, Y. M. (2011). Reconsidering Political Cynicism and Political Involvement: A Test of Antecedents. American Communication Journal .Harris, A. L. (1996). Political marketing - vive la difference! European Journal Of Marketing , 14-24.Humsona, S. P. (2017). Social Media in Political Marketing: A Study of Teman Ahok. The 3rd International Conference on Social and Political Science (p. 4). Knowledge E.Husser, H. &. (2012). The ratio of people's evaluation of government performance relative to their normative expectations of how government ought to perform.Irawan, I. A. (2018, August 2). Milenial dan Pilpres 2019. Retrieved December 14, 2018, from Kumparan: https://kumparan.com/erucakra-garuda-nusantara/millenial-dan-pilpres-2019-27431110790558842Jamshed Butt, M. A. (2017). Intention for Voting in Pakistan: The Role of Social Media, Ethnicity and Religiosity. International Journal of Multicultural and Multiregiligous Understanding , 1-15.Jensen, T. H. (2007). Understanding Voters' Decisions: A Theory of Planned Behaviour Approach. Innovative Marketing, LLC "Consulting Publishing Company "Business Perspectives".Jimenez, O. F. (2012). Election campaigns, the media and their impact on civic engagement of Mexicans in the 2012 Presidential Election. Universidad de Guanajuato, Departmento de Estudios Politicos y de Gobierno, Mexico.Juditha, C. (2015). Political Marketing and Social Media: Study of Political Marketing by RI Presidential Candidates 2014 in Facebook. Jurnal Studi Komunikasi dan Media .Kelly Opdycke, P. S. (2013). The Effects of Political Cynicism, Political Information Efficacy and Media Consumption on Intended Voter Participation. 75-97.Kennedy. (2008). The importance of good sampling [Online]. available at: http://www.coronainsights.com/2008/08/the-importance-of-good-sampling/ , Accessed on 21 January 2019.Komiak, S. Y. (2006). The effects of personalization and familiarity on trust and adoption of recommendation agents.Malhotra, N. K. (2010). Marketing Research : An Applied Orientation sixth edition. PEARSON EDUCATION.Marika Steenkamp, N. H.-C. (2014). The use of Facebook for political commentary in South Africa.Marquis, L. (2010). Understanding Political Knowledge and Influence on Voting Preferences in the 2007 Federal Election. Swiss Political Science Review 16(3): 425-56.McMillan, & James, H. (2011). Educational Research:Fundamental for the Consumers, 2nd ed. pp. 258-359.McNeal, C. J. (2003). Unraveling the Effects of the Internet on Political Participation? University of Utah. Sage Publications, Inc.Meet the millennials: Who are Generation Y? (2017, August 28). Retrieved December 14, 2018, from BBC: https://www.bbc.com/news/uk-scotland-41036361Menon, S. V. (2008). Political Marketing: A Conceptual framework. Munich Personal RePEc Archive .Newman, B. I. (1994). The Marketing of The President: Political Marketing As Campaign Strategy. California, United States of America: Sage Publications, Inc.Nicholas A. Christakis, J. H. (2011). Connected: The Amazing Power of Social Networks and How They Shape Our Lives.Nursal, A. (2004). Political Marketing, Strategi memenangkan pemilu. Jakarta: PT. Gramedia Pustaka Utama.O'Cass, A. (1996). Political marketing and the marketing concept. European Journal of Marketing , 37-53.Omega. E-commerce: the role of familiarity and trust.Omrod, R. P. (2013). Defining Political Marketing. Denmark: Aarhus University .Pemilihan umum Presiden Indonesia 2019. (n.d.). Retrieved January 19, 2019, from Wikipedia: https://id.wikipedia.org/wiki/Pemilihan_umum_Presiden_Indonesia_2019Popham, W. J. (2008). Transformative Assessment. United States: Houghton Mifflin Harcourt.Prasetyo, B., & Jannah, L. M. (2012). Metode Penelitian Kuantitativ (7th ed). Jakarta: Rajagrafindo Persada.Rahmawati, I. (2014). Social Media, politics and young adults: The impact of social media use on young adults' political efficacy, political knowledge and political participation towards 2014 Indonesia General Election. Master Thesis, University of Twente, Faculty of Behavioral Science, Communication Studies, Media and Communication.Sangwon Lee, M. X. (2018). Social Distraction? Social Media Use and Political Knowledge in Two U.S. Presidential Elections. Computers in Human Behavior.Saraswati, M. S. (2018). Social Media and the Political Campaign Industry in Indonesia. Jurnal Komunikasi ISKI (Ikatan Sarjana Komunikasi Indonesia) .Scheufele, K. E. Finally Informing the Electorate? How the Internet Got People Thinking about Presidential Politics in 2004.Sekaran, U. (2003). Research Method for Business. John Wiley & Son.Sekaran, U., & Bougie, R. (2011). Research Methods for Business: skill-Building approach (1st ed). United Kingdom: John Wiley & Sons Ltd.Serek, J. &. (2015). Changes in late adolescents' voting intentions during the election campaign: Disentangling the effects of political communication with parents, peers and media. European Journal of Communication.Setyowati, D. (2018, July 18). LIPI: 60% Anak Muda Akses Berita Politik Lewat Media Sosial. (P. Aria, Editor) Retrieved November 03, 2018, from katadata.co.id: https://katadata.co.id/berita/2018/07/18/lipi-60-anak-muda-akses-berita-politik-lewat-media-sosialSeyd, B. (2016). How Should We Measure Political Trust. PSA annual conference. Brighton: University of Kent.Shamma, D. F. (2014, March). Factors influencing voting intentions for Egyptian parliament election 2011. Journal of Islamic Marketing .Sheth, B. I. (1985). A Model of Primary Voter Behavior. The Journal of Consumer Research .Sigit Pranawa, R. H. (2016). Social Media in Political Marketing: A Study of Teman Ahok. The Impact of Information Technology on Social and Political Dynamics .Simarmata, S. (2015, October). The Modernization of Election Campaign and its research opportunites in Indonesia's Direct Elections Era. 2nd International Conference on Corporate and Marketing Communication .Stromback, S. G. (2018). Patterns of intra election volatility the impact of political knowledge. Informa, Journal of Elections, Public Opinion and Parties.Sugiyono. (2014). Metode Penelitian Pendidikan Pendekatan Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.Sutarso, J. (2011). Pendekatan Pemasaran Politik (Political Marketing) Dalam Pemilihan Umum. University of Muhammadiyah, Jurusan Ilmu Komunikasi, Fakultas Komunikasi dan Informatika, Surakarta.Swartley, M. (2018). Political Marketing: How Social Media influenced the 2008-2016 Presidential Elections and Best Practices Associated. Liberty University.Tabroni, R. (2014). Marketing politik: media dan pencitraan di era multipartai. Graha Ilmu.The role played by social media in political participation and electoral campaigns. (2014, December 02). Retrieved December 07, 2018, from European Parliamentary Research Service Blog: https://epthinktank.eu/2014/02/12/the-role-played-by-social-media-in-political-participation-and-electoral-campaigns/Toka, G. Political Knowledge and Voter Inequality. Entral European University, Hungary & University of Oxford, United Kingdom.Toka, G. (2006). Political Knowledge and Voter Inequality. Central European University, Hungary & University of Oxford, United Kingdom. Marie Curie Intra-European Fellowship.Uthe. (2014, July 9). Lebih 200 Juta Interaksi Facebook Warnai Pilpres 2014. Retrieved 5 7, 2019, from Business Lounge Journal: http://blj.co.id/2014/07/09/perang-facebook-warnai-pilpres-2014/Vesnic-Alujevic, L. (2012). Political participation and web 2.0 in Europe: A case study of Facebook. Public Relations Review.Vinzi, V. E., Chin, W. W., Henseler, J., & Wang, H. (2010). Handbook of Partial Least Square: Concepts, Methods and Applications. Newyork: Springer Publication.Ware, A. Political Knowledge and Political Ignorance: a re-examination. University of Warwick, Department of Politics.Wojciech Cwalina, A. F. (2014). Advanced Theory of Political Marketing. In W. K. Tadeusz Marek, Human Factors of a Global Society (pp. 245-248). Boca Raton, London and New York: CRC Press, Taylor & Francis Group.Wojciech Cwalina, A. F. (2015). Political Marketing Theoretical and Strategic Foundations. London and New York: Routledge Taylor & Francis Group.Yadav, M. S. (2005). Interactivity in the electronic marketplace: an exposition of the concept and implications for research. Journal of the Academy of Marketing Science.Zikmund, W. (2010). Business Research Methods (8th ed). Canada: Cengange Learning.